2013
DOI: 10.1021/bi301421v
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Insights into the Regulation ofHelicobacter pyloriArginase Activity by an Evolutionary Nonconserved Motif

Abstract: Urea producing bimetallic arginases are essential for the synthesis of polyamine, DNA, and RNA. Despite conservation of the signature motifs in all arginases, a nonconserved 153ESEEKAWQKLCSL165 motif is found in the Helicobacter pylori enzyme, whose role is yet unknown. Using site-directed mutagenesis, kinetic assays, metal analyses, circular dichroism, heat-induced denaturation, molecular dynamics simulations and truncation studies, we report here the significance of this motif in catalytic function, metal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 48 publications
(94 reference statements)
1
25
0
Order By: Relevance
“…DFT studies were performed to help understand the basis for these changes. 3 ]-(OTf) 2 (4) were synthesized by using similar methods but by altering either the cobalt salt or the solvent to achieve the respective complexes. For example, 1 was obtained by treating cobalt(II) triflate with T1Et4iPrIP (1 equiv.)…”
Section: Introductionmentioning
confidence: 99%
“…DFT studies were performed to help understand the basis for these changes. 3 ]-(OTf) 2 (4) were synthesized by using similar methods but by altering either the cobalt salt or the solvent to achieve the respective complexes. For example, 1 was obtained by treating cobalt(II) triflate with T1Et4iPrIP (1 equiv.)…”
Section: Introductionmentioning
confidence: 99%
“…62,67 However, due to the absence of the analogous 13-residue insertion sequence in other homologs, in the model structure this stretch was found as a loop and present on the surface of the protein. 60 This also could not explain the possible role of the motif in structure or function.…”
Section: A Nonconserved Motif Of H Pylori Arginase Is Vital To the En...mentioning
confidence: 97%
“…Srivastava et al performed detailed sequence analysis and showed that this stretch is not present in the other homologs. 60 To obtain insight into this motif's role in structure and function, they performed molecular dynamics (MD) simulations studies using the model structure of H. pylori apoarginase for 450 ns. During the simulations, this motif was found to move towards the active site and forms a loop-cum-helix structure.…”
Section: A Nonconserved Motif Of H Pylori Arginase Is Vital To the En...mentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterium has a unique mechanism to survive in the acidic environment of the stomach lumen (pH ∼1–2) and colonizes near the mucosal layer, where the pH is around 5–7 . The acid protection is conferred by H. pylori arginase (RocF), a well‐studied enzyme that utilizes L‐arginine to generate urea and L‐ornithine Further, the degradation of urea to ammonia by urease elevates the pH of the microenvironment , which helps in the survival of the bacterium. Like other arginine decarboxylases (ADCs), the H. pylori enzyme has been shown to catalyze the conversion of L‐arginine to agmatine and CO 2 .…”
Section: Introductionmentioning
confidence: 99%